Development of directions for increasing the efficiency of innovation management taking into account decarbonization trends in the context of international cooperation - Ivanova, Maryna; Varyanichenko, Olena; Sannikova, Svitlana; Tryfonova, Olena; Bohach, Kyrylo (Eastern-European Journal of Enterprise Technologies, 2025)
The most important area in the fight against negative climate changes and ensuring sustainable development is the decarbonization of the economy. The object of this study is the development trends in decarbonization to enable effective innovation management processes under the conditions of international cooperation. Decarbonization involves reducing carbon dioxide emissions by switching to renewable energy sources, increasing energy efficiency, and introducing innovative technologies. As a global trend, it requires coordinated actions at all levels – from national governments to the private sector and international organizations. The possibilities of ensuring decarbonization through the use of climate-neutral energy complexes have been assessed. A feature of the approach is the use of statistical analysis to identify trends in the development of decarbonization of the economy. This has made it possible to prove with a probability of 98.6 % that if the trends of recent years regarding the increase in the number of operating nuclear reactors prevail, by the end of 2030 their number in the world will reach 489 units. The practical value of using wind power plants of different capacities and small modular reactors (SMRs) to provide electric vehicles with energy has been substantiated. This is confirmed by calculations of the number of cars that can be supplied with electricity from wind stations of various capacities at certain values of the capacity factor. In contrast to conventional approaches, determining the areas of innovative management allows the implementation of decarbonization processes under the conditions of international cooperation. The use of wind power plants of various capacities is of practical interest; the expediency of using small modular reactors and supplying electric vehicles with energy has been assessed